Penyediaan indeks kos bangunan - Khalid, Abdul Ghani (Universiti Teknologi Malaysia, 2003)
The development of tender price index for housing is necessary as guidance for. quantity surveyors in estimating the tender price for housing projects. This research was executed to generate the tender price index for housing. The Jadual Kadar Harga Jabatan Keija Raya (JKR) 2001 (JKR 20800-117-2001) was used as a base year. This is caused by the lack of data collected which is compulsory to develop the base rate of 2001. The base index value for the year of 2001 was assumed to be 100. The Methodology of Construction of Tender Price Index and Work Example, Building Cost Information Centre, Institution of Surveyor, Malaysia (ISM was applied with some modifications including the arrangement of elements in accordance to Elemental Cost Analysis and excluding the external works element. The Bill of Quantity of a double storey terrace house for the year of 1999 utilized as a sample to demonstrate the index calculations. Analysis on the intermediate unit of a double storey terrace house projects in the year of 1997 to 2000 have been executed and a tender price indices was successfully developed. The result shows that the price of a tender can be affected by the economics strength of the country.